2017
DOI: 10.1111/dmj.12034
|View full text |Cite
|
Sign up to set email alerts
|

Design Research: Off the Rails or on the Right Track?

Abstract: If research findings remain unknown, they are unlikely to improve design processes and outcomes. While design scholars have lamented the lack of research utilization by practitioners, some designers have derided their efforts. While scholars have outlined strategies to decrease the research utilization gap, these are largely one‐sided suggestions and have lacked widespread implementation and testing. As such, a great deal of information likely remains out of the hands of those who could use it when making deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 74 publications
(123 reference statements)
2
8
0
Order By: Relevance
“…Given that the rate of change is seemingly more pronounced in recent years, problems surrounding the use of research may be even more prevalent today. While design discourse continues to emphasize the role of research and information in improving project outcomes (Bosch & Nanda, ; McCuskey Shepley & Danko, ; Whitemyer, ), promoting design innovation (Gensler, ; HKS, ; Perkins & Will, ), and enhancing a firm's competitive stance (Davis, ), evidence suggests a persistent and pervasive gap between scholarly research and the expectations of design practitioners (Huber, ; Martin, ; Sommer, ). Farbstein and Kantrowitz () suggested that this was due to traditional design research being “divorced (in time and persona)” from design decision‐making (p. 298).…”
Section: Purposementioning
confidence: 99%
See 4 more Smart Citations
“…Given that the rate of change is seemingly more pronounced in recent years, problems surrounding the use of research may be even more prevalent today. While design discourse continues to emphasize the role of research and information in improving project outcomes (Bosch & Nanda, ; McCuskey Shepley & Danko, ; Whitemyer, ), promoting design innovation (Gensler, ; HKS, ; Perkins & Will, ), and enhancing a firm's competitive stance (Davis, ), evidence suggests a persistent and pervasive gap between scholarly research and the expectations of design practitioners (Huber, ; Martin, ; Sommer, ). Farbstein and Kantrowitz () suggested that this was due to traditional design research being “divorced (in time and persona)” from design decision‐making (p. 298).…”
Section: Purposementioning
confidence: 99%
“…While the design industry is not alone in facing the research utilization gap, it does face a particular set of regulatory and economic conditions that can make the rift particularly pervasive and persistent. First, interior environments are not patented, nor is a designer's process trademarked; thus, the design industry lacks many of the incentives and protections offered by intellectual property laws (Huber, ; Whitemyer, ). Second, research funding in both public and private sectors is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations